Upaya Guru PAI dalam Meningkatkan Motivasi Belajar Siswa di Sma Hidayatus Salam Lowayu Dukun Gresik - Kusuma Ningtias, Ratih; Mahbubah, Zaimatul (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
The Purposes of this study were to: (1) Describe the efforts of PAI teachers in increasing students’ learning motivation at SMA Hidayatus Salam Lowayu Dukun Gresik. (2) Describe the obstacles experienced by PAI teachers in increasing students’ learning motivation at SMA Hidayatus Salam Lowayu Dukun Gresik. (3). Describe the solutions that PAI teachers do in increasing students’ learning motivation at SMA Hidayatus Salam Lowayu Dukun Gresik.The research used a qualitative research as approach as approach and case study as research design. The data collection used observation, interview, and documentation techniques: The data analysis used following steps reduction, display and draw conclusions.The results of this study indicate that: (1) The forms of PAI teachers' efforts in increasing students' learning motivation at Hidayatus Salam Lowayu Dukun Gresik High School such as: giving grades from student learning outcomes, giving praise and prizes, giving tests and assignments, using learning methods that varied in teaching, using learning media and giving punishment. (2) Obstacles faced by PAI teachers in increasing student motivation at Hidayatus Salam Lowayu Dukun Gresik High School are as follows: when teachers use learning methods to increase learning motivation, some students are a bit slow in the learning process. Meanwhile, when teachers use learning media to increase learning motivation, students have different grasping powers, students who have less understanding will find it difficult to understand the material taught by the teacher. And the obstacle faced by the teacher itself is the use of learning methods and media in the material being taught. Meanwhile (3) the solution that the PAI teacher does in overcoming these obstacles or problems is to provide opportunities for children to consult with the teacher regarding the obstacles he is experiencing, use various learning methods and learning media, maintain interest, willingness and enthusiasm for learning in students, create an attractive learning environment, provide learning agreements or contracts, provide punishments that build students up.